2004
DOI: 10.1039/b405061d
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-induced photoelectrochemistry at metal nanoparticles supported on nanoporous TiO2

Abstract: Nanoporous TiO(2) films loaded with gold and silver nanoparticles exhibit negative potential changes and anodic currents in response to visible light irradiation, so that the films would potentially be applicable to inexpensive photovoltaic cells, photocatalysts and simple plasmon sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
338
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 463 publications
(364 citation statements)
references
References 18 publications
10
338
3
2
Order By: Relevance
“…In those approaches, metal nanostructures act as passive elements that introduce parasitic ohmic losses. However, it was shown recently that, a direct photoelectric energy conversion from light absorbed in the metal is within reach, by properly harnessing the hot-electron population derived from the Landau damping of these plasmonic resonances, [9][10][11][12][13][14][15][16][17][18][19][20] This opens the exciting possibility of a new sensing and light harvesting technology, whose spectral response can be tailored by properly modifying the topology of a metal nanostructure, and is beyond the band-to-band absorption paradigm in traditional semiconductors. 11 Theoretical predictions set maximum photovoltaic power conversion efficiencies that range from 10% to 22% depending on the applied model for hot electron population and emission.…”
Section: Introductionmentioning
confidence: 99%
“…In those approaches, metal nanostructures act as passive elements that introduce parasitic ohmic losses. However, it was shown recently that, a direct photoelectric energy conversion from light absorbed in the metal is within reach, by properly harnessing the hot-electron population derived from the Landau damping of these plasmonic resonances, [9][10][11][12][13][14][15][16][17][18][19][20] This opens the exciting possibility of a new sensing and light harvesting technology, whose spectral response can be tailored by properly modifying the topology of a metal nanostructure, and is beyond the band-to-band absorption paradigm in traditional semiconductors. 11 Theoretical predictions set maximum photovoltaic power conversion efficiencies that range from 10% to 22% depending on the applied model for hot electron population and emission.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these recent metal-TiO2 Schottky diode structures [37][38][39][40][41][42][43][44][45][46][47], it would appear that the barrier layer was actually quite a bit thicker than 10 nm (probably in excess of 1 um) and further details was unable to be found in these papers. Semi-classical models did not account for non-equilibrium energy distributions of carriers, or do so through a localize lattice temperature.…”
Section: Theoretical Modeling Of Ag-tio2-ti Mim Diodesmentioning
confidence: 92%
“…First, Tatsuma et al [37,38,45] and other workers [42,46] proposed that the photoexcited electrons in the metal nanoparticles transferred from the metal particle to the TiO2 conduction band since the photoresponse of these metal-TiO2 diode structures was consistent with the absorption spectra of Au or Ag nanoparticles. Second, Kamat et al [43,44] and Li et al [47] have suggested that the noble metal nanoparticles act as electron sinks or traps in the metal-TiO2 diode structures to accumulate the photogenerated electrons, which could minimize charge recombination in the semiconductor films.…”
Section: Review Of Metal-insulator-metal (Mim) Diodesmentioning
confidence: 99%
See 2 more Smart Citations